Abiraterone acetate plus prednisolone for metastatic patients starting hormone therapy: 5‐year follow‐up results from the STAMPEDE randomised trial (NCT00268476). Issue 3 (16th May 2022) - James, Nicholas D.; Clarke, Noel W.; Cook, Adrian; Ali, Adnan; Hoyle, Alex P.; Attard, Gerhardt; Brawley, Christopher D.; Chowdhury, Simon; Cross, William R.; Dearnaley, David P.; de Bono, Johann S.; Diaz‐Montana, Carlos; et al.
Abstract: Abiraterone acetate plus prednisolone (AAP) previously demonstrated improved survival in STAMPEDE, a multiarm, multistage platform trial in men starting long‐term hormone therapy for prostate cancer. This long‐term analysis in metastatic patients was planned for 3 years after the first results. Standard‐of‐care (SOC) was androgen deprivation therapy. The comparison randomised patients 1:1 to SOC‐alone with or without daily abiraterone acetate 1000 mg + prednisolone 5 mg (SOC + AAP), continued until disease progression. The primary outcome measure was overall survival. Metastatic disease risk group was classified retrospectively using baseline CT and bone scans by central radiological review and pathology reports. Analyses used Cox proportional hazards and flexible parametric models, accounting for baseline stratification factors. One thousand and three patients were contemporaneously randomised (November 2011 to January 2014): median age 67 years; 94% newly‐diagnosed; metastatic disease risk group: 48% high, 44% low, 8% unassessable; median PSA 97 ng/mL. At 6.1 years median follow‐up, 329 SOC‐alone deaths (118 low‐risk, 178 high‐risk) and 244 SOC + AAP deaths (75 low‐risk, 145 high‐risk) were reported. Adjusted HR = 0.60 (95% CI: 0.50‐0.71; P  = 0.31 × 10 −9 ) favoured SOC + AAP, with 5‐years survival improved from 41% SOC‐alone to 60% SOC + AAP. This was similar in low‐risk (HR = 0.55; 95% CI: 0.41‐0.76) and high‐risk (HR = 0.54; 95% CI: 0.43‐0.69) patients. Median and current maximum time on SOC + AAP was 2.4 and 8.1 years. Toxicity at 4 years postrandomisation was similar, with 16% patients in each group reporting grade 3 or higher toxicity. A sustained and substantial improvement in overall survival of all metastatic prostate cancer patients was achieved with SOC + abiraterone acetate + prednisolone, irrespective of metastatic disease risk group. Abstract : What's new? Initial results from the STAMPEDE trial for advanced prostate cancer showed that adding abiraterone acetate and prednisone (AAP) to androgen deprivation therapy improved progression‐free survival. Here, the authors present long‐term results of metastatic patients in the STAMPEDE trial. Median follow‐up increased from 52 to 73 months. They found that AAP improved overall survival of all metastatic prostate cancer patients, whether their disease was high‐risk or low‐risk.